NILAI NILAI KEJADIAN 2:8-17 SEBAGAI LANDASAN PEMBELAJARAN BERBASIS KARAKTER DI SEKOLAH MENENGAH PERTAMA - Plestari, Delsi (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
This study explores the application of values from Genesis 2:8-17 as a foundation for responsible character education at Kartika Junior High School, Surabaya. Using a qualitative descriptive-explorative approach, the research involved 15 Christian students, Christian education teachers, and parents for data triangulation. Data were collected through interviews, observations, and document analysis. The findings show that integrating biblical values enhances students’ responsibility, discipline, and spiritual awareness. Genesis 2:8-17 encourages students to be accountable to God, others, and the environment. Collaboration between teachers and parents strengthens holistic character development. This study highlights the importance of integrating spiritual values into character education and fills a research gap in contextual applications of Genesis in junior high school learning. It offers a practical model for biblical values integration involving active roles from both school and family in shaping students' character and spirituality in a holistic manner.